Summit of the N=40 island of inversion: precision mass measurements and ab initio calculations of neutron-rich chromium isotopes - Silwal, Roshani; Andreoiu, C.; Ashrafkhani, B.; Bergmann, J.; Brunner, T.; Cardona, J.; Dietrich, Kilian; Dunling, E.; Gwinner, G.; Hockenbery, Z.; Holt, J. D.; Izzo, C.; et al. (Physics letters, 2022)
Mass measurements continue to provide invaluable information for elucidating nuclear structure and scenarios of astrophysical interest. The transition region between the Z=20 and 28 proton shell closures is particularly interesting due to the onset and evolution of nuclear deformation as nuclei become more neutron-rich. This provides a critical testing ground for emerging ab-initio nuclear structure models. Here, we present high-precision mass measurements of neutron-rich chromium isotopes using the sensitive electrostatic Multiple-Reflection Time-Of-Flight Mass Spectrometer (MR-TOF-MS) at TRIUMF's Ion Trap for Atomic and Nuclear Science (TITAN) facility. Our high-precision mass measurements of 59,61−63Cr confirm previous results, and the improved precision in measurements of 64−65Cr refine the mass surface beyond N=40. With the ab initio in-medium similarity renormalization group, we examine the trends in collectivity in chromium isotopes and give a complete picture of the N=40 island of inversion from calcium to nickel.
Gesehen am 09.03.2023